The Effect of Investment Knowledge, Lifestyle, and Income on Antam Gold Investment Decisions Using Gold (E-Gold) in the BSI Application (Case Study on Generation Z Muslims of Lumajang Regency) - Nur Halimah; Khamdan Rifa’i; Hersa Farida Qoriani (Universitas KH. Abdul Chalim Mojokerto, 2025)
Investment decisions involve an investor's actions to invest funds in various investment options, both in the form of financial assets and real assets. The formulation of the problem in this study is how does investment knowledge affect the Antam E-Gold Investment decision?, How does lifestyle affect the Antam E-Gold Investment decision? How does income affect the Antam E-Gold Investment decision? The method used is quantitative. The results of the study showed that the partial test results of the investment knowledge variable had a positive effect on the Antam E-Gold Investment Decision. The Lifestyle variable did not affect the Antam E-Gold Investment Decision and the income variable had a positive effect on the Antam E-Gold Investment Decision.